2022
DOI: 10.1186/s12891-022-05122-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adverse events after percutaneous pedicle screws fixation in patients with single-segment thoracolumbar burst fractures

Abstract: Background Percutaneous pedicle screw fixation (PPSF) is the primary approach for single-segment thoracolumbar burst fractures (TLBF). The healing angle at the thoracolumbar junction is one of the most significant criteria for evaluating the efficacy of PPSF. Therefore, the purpose of this study was to analyze the predictors associated with the poor postoperative alignment of the thoracolumbar region from routine variables using a support vector machine (SVM) model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…We will compare different ML classifiers such as logistic regression (LR) which fits better for dichotomous data [ 43 , 44 ], K nearest-neighbor (KNN) [ 45 , 46 ], Linear Discriminant Analysis (LDA) [ 45 , 47 , 48 ], support vector machine (SVM) [ [49] , [50] , [51] ], and CNN [ 40 , 41 ] to determine if there is a better predictive ML model.…”
Section: Discussionmentioning
confidence: 99%
“…We will compare different ML classifiers such as logistic regression (LR) which fits better for dichotomous data [ 43 , 44 ], K nearest-neighbor (KNN) [ 45 , 46 ], Linear Discriminant Analysis (LDA) [ 45 , 47 , 48 ], support vector machine (SVM) [ [49] , [50] , [51] ], and CNN [ 40 , 41 ] to determine if there is a better predictive ML model.…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of using artificial intelligence to predict the development of kyphosis disease is its ability to predict the development of kyphosis using radiological parameters that are not traditionally used to predict the development of kyphosis; for example, Dong et al [23] demonstrated that a support vector model was able to identify multiple variables associated with the development of postoperative kyphosis disease in patients who underwent percutaneous pedicle screw fixation after thoracolumbar burst fracture with favorable predictive performance, and the identified variables included intervertebral disc injury, surgically corrected Cobb angle, preoperative Cobb angle, and intervertebral distance. Predicting the development of postoperative kyphosis disease is difficult, and these are not parameters traditionally used to predict the development of postoperative kyphosis disease, so it is very advantageous that artificial intelligence can identify relevant variables and utilize these variables to predict the development of kyphosis disease.…”
Section: Discussionmentioning
confidence: 99%
“…Case selection is a critical factor in opting for MIPS fixation to avoid the risk of a postoperative deformity or lifelong kyphosis [10]. Literature consensuses suggest that conservative treatment is not advisable in type A3 burst fractures [AO-Magerl classification] [3], young active individuals avoiding prolonged work absence, obesity, polytrauma, and previous deep venous thrombosis (DVT) patients.…”
Section: Introductionmentioning
confidence: 99%